Translators in Fabula: Bridging Transfiction and Translator Studies through a Comparative Analysis of Contemporary Italian Narratives - Bergantino, Andrea (Trinity College Dublin. School of Lang, Lit. & Cultural Studies. Discipline of Russian, 2024)
The presence of translators as characters in literary texts was first named “transfiction” in 2014 (Kaindl, 3-4). Much research to date on transfiction takes the form of isolated case studies, being largely influenced by methods and perspectives originating in the field of Comparative Literature. This thesis contributes to knowledge by asking, not only about the characteristics of translator-characters’ representation, but also how the materials, methods, and findings of transfiction research may become useful to Translator Studies and Translation Studies more generally. While continuing the tradition of close reading as its central method, the thesis adopts a wider methodological approach that walks the line between fiction and academic literature, by contrasting the literary depiction of translators with their academic description. The thesis presents the analysis conducted on its sources in the form of five case studies that, collectively, form a multiple-case study of contemporary Italian transfiction. Contextually, its primary focus is on the human translator, rather than on translation as a product and process. Given the key roles played by translation and translators in Italian culture, the thesis is anchored in the Italian context, exploring eleven primary sources that span the 1960s to the 2020s. These sources include novels and short stories, with some of their authors having first-hand experience as translators and others having no background in translation. In addition, these materials include works authored in Italian by first- language speakers, as well as Italian as an exophonic, adopted language. This study engages with a variety of themes related to the human translator that range from translatorial clichés and the trope of translator (in)visibility, to the role of the human translator in connection with the more-than-human. It harnesses the potential of various forms of fiction to inform and develop Translator Studies, fostering a humanised approach to the wider domain of Translation Studies.
APPROVED
Keywords: transfiction; translation studies; translator studies; contemporary Italian literature